Encouraging medical students to become self-directed learners through conduction of small-group learning sessions - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
In the field of medical education, learning among medical students is found to be deeper and more effective, when it happens in small groups. This is primarily because the small-group learning environment enables students to become self-directed learners and also gives them an opportunity to collaborate with other members of the group. An effective small-group learning session will depend upon the discussion skills of the teacher and the students and essentially includes appropriate questioning, listening patiently to the responses of others, responding to the raised questions in a polite and meaningful manner, explanation of the given problem, ensuring active preparation for the session, and smart opening and closure of the sessions. In conclusion, the conduction of an effective small-group learning sessions helps the medical student to become self-directed learner and improve their critical thinking and clinical reasoning skills. It is quite essential that all the medical colleges should include small-group learning sessions within their teaching schedule and help the students to acquire subject competencies.